Prevalence of erythromycin and clindamycin resistance among Streptococcus agalactiae isolates in Germany - Schöning, Tilman; Wagner, J.; Arvand, Mardjan (Clinical microbiology and infection, 2005)
The antimicrobial susceptibilities of 338 clinical Streptococcus agalactiae isolates from two geographical regions in Germany were determined by agar dilution. All isolates were susceptible to penicillin, cefotaxime and vancomycin. The overall frequencies of erythromycin and clindamycin resistance were 11% and 4.7%, respectively. Determination of resistance phenotypes among the 37 erythromycin-resistant isolates revealed constitutive and inducible MLSB resistance in 40.6% and 37.8% of isolates, respectively, and susceptibility to clindamycin in 21.6% of isolates. Only 14.3% of isolates with inducible MLSB resistance were identified as clindamycin-resistant by determination of clindamycin MICs. Pulsed-field gel electrophoresis suggested a clonal distribution pattern among the erythromycin-resistant isolates.
Gesehen am 07.07.2022